Learning-Related Plasticity in PE1 and Other Mushroom Body-Extrinsic Neurons in the Honeybee Brain - Okada, Ryuichi (J Neurosci, 2007)
Extracellular recording were performed from mushroom body-extrinsic neurons while the animal was exposed to differential conditioning to two odors, the forward-paired conditioned stimulus (CS+; the odor that will be or has been paired with sucrose reward) and the unpaired CS− (the odor that will be or has been specifically unpaired with sucrose reward). A single neuron, the pedunculus-extrinsic neuron number 1 (PE1), was identified on the basis of its firing pattern, and other neurons were grouped together as non-PE1 neurons. PE1 reduces its response to CS+ and does not change its response to CS−after learning. Most non-PE1 neurons do not change their responses during learning, but some decrease, and one neuron increases its response to CS+. PE1 receives inhibitory synaptic inputs, and neuroanatomical studies indicate closely attached GABA-immune reactive profiles originating at least partially from neurons of the protocerebral–calycal tract (PCT). Thus, either the associative reduction of odor responses originates within the PE1 via a long-term depression (LTD)-like mechanism, or PE1 receives stronger inhibition for the learned odor from the PCT neurons or from Kenyon cells. In any event, as the decreased firing of PE1 correlates with the increased probability of behavioral responses, our data suggest that the mushroom bodies exert general inhibition over sensory–motor connections, which relaxes selectively for learned stimuli.